Adolescent Experience with Unwanted Pregnancy: A Scoping Review - Ngaisah Tri Rahayu; Mufdillah Mufdillah; Farida Kartini (Universitas 'Aisyiyah Yogyakarta, 2021)
Teenagers who experience unwanted pregnancy will drop out of school, not accept pregnancy, be ostracized, and plan to have an abortion. Arksey and O'Malley methodology. The databases are Pubmed, Proquest, Sciendirect and Wiley. Review articles using JBI is grade A as much as 5 articles and 2 articles grade B. Psychological impact experienced by teenagers with unwanted pregnancy is an emotional initial reaction, when knowing she is pregnant will be shocked and angry, feel hopeless, and intend to commit suicide because she can not continue her education so that it requires support from family, friends, spouse and the environment.